Operationalizing the Dasa-Rāja Dhamma: A Buddhist Framework for Employee and Customer Satisfaction “A Study of Nepal Telecom, Itahari” - Thapa, Prasanna (Prajñā Journal of Buddhist Studies, 2026)
Customer satisfaction metrics within service organizations include efficiency, responsiveness, and loyalty metrics, but these metrics tend to lack capturing the impact of internal employee well-being on service quality. This paper describes a management approach to applying Dasa-Rāja Dhamma “Ten Royal Virtues,” specifically within Nepal Telecom to improve internal employee satisfaction and customer satisfaction. The Dasa-Rāja Dhamma: dāna (generosity), sīla (morality), pariccāga (self-sacrifice), ājjava (honesty), maddava (gentleness), tapa (self-restraint), akkodha (non-anger), avihimsa (non-violence), khanti (patience), and avirodhana (uprightness) was originally designed as a prescriptive guide for righteous rule in Buddhist textual traditions. However, in this research work, dāna (generosity), sīla (morality), pariccāga (self-sacrifice), ājjava (honesty), maddava (gentleness), tapa (self-restraint), akkodha (non-anger), avihimsa (non-violence), khanti (patience), and avirodhana (uprightness), and so on, are reframed and redefined as organizational and behavioral axioms in forming a unified framework of Buddhist management. At Nepal Telecom's FTTH services, issues of organizational bureaucracy and lack of accountability and fairness in work distribution are also met and managed Insofar as this paper situates the Dasa-Rāja Dhamma within a formalized Buddhist management theory, its contribution lies at the intersection of both management theory research and Buddhist studies, specifically in resolving how internal worker satisfaction impacts the underlying catalyst for superior customer satisfaction.